Sandwiched between a rock and a hard place? - LAM, Thomas (Institutional Knowledge at Singapore Management University, 2022)
The policy gap between US and China is likely to be widening further, potentially raising and unevenly distributing the risks of negative spillovers for Asia and the rest of the world.